An Analysis of Barrett’s Taxonomy’s Applications in Teacher Association (MGMP) Published English Workbooks (LKS) for Senior High Schools in Padang - Muhammad Alhadi; Yetti Zainil (Journal of English Language Teaching, 2023)
This research aimed to analyse questions included in English Teacher Association (MGMP) Published English Workbooks (LKS) for Senior High School in Padang based on Barrett’s Taxonomy in Reading Comprehension. The taxonomy consists of five stages which are “Literal Comprehension,” “Reorganization,” “Inferential Comprehension,” “Evaluation,” and “Appreciation.” The research design used for this research is descriptive qualitative, and the instruments used to gather necessary data are an observation checklist and interview questions. The analysed questions were classified based on the stages of Barrett’s taxonomy. The result of the analysis showed that from all the reading comprehension questions in all the workbooks observed, Inferential Comprehension is the stage that is applied by the questions the most, which is at 48.2%, followed by Literal Comprehension at 42.5%, Reorganization at 8%, Appreciation at 1%, and Evaluation at 0.3% of the total questions observed. Although all the stages of Barrett’s taxonomy are present in the workbooks, it does not imply that the taxonomy has been applied in the MGMP Published Workbooks, for the percentages of the questions from each stage do not resemble the recommended rates proposed for each of the stage. In addition to that, by interviewing members of the writing team of the workbooks, it was found that Barrett’s taxonomy had never been applied when constructing questions for the workbooks. This backs up the previous idea that Barrett’s was not applied in MGMP Published English workbooks.